Synthesis and characterisation of Mo(IV) complexes of 2,3-dihydroxybenzaldehyde Schiff Bases and their activity against cancer cell lines - Rohaiza, S.O, Sharifah; M.A, Hapipah,; Zawawi, Y, Mohd; M.Z, Sharifuddin,; A.W, Norhanom,; S.M, Rahuma, (Malaysian Journal of Science, 2001)
Schiff base ligands (SB) have been prepared by condensation of 2,3-dihydroxybenzaldehyde with aromatic amines in either absolute ethanol or methanol. The products reacted with MoCl5 in MeCN in a 1:1 stoichiometry in the presence of triethylamine to afford [MoCl2(SB)2]. The Schiff bases and the molybdenum complexes have been characterized by elemental analysis, IR,1H NMR and 13C NMR spectroscopic methods. The anti-tumour test was conducted on the ligands and the complexes. The tumour growth inhibitory activity of the Schiff bases and their derivatives are reported.